INSTRUCTING STUDENTS TO WORK IN AN IMPROVISATIONAL ENVIRONMENT (Universal International Scientific Journal, 2026)
This article discusses the pedagogical significance, methods and effective approaches to directing students to improvisational active work in the environment. The use of improvisational elements in the educational process is analyzed to develop students' independent thinking, quick decision-making, creative approach and communicative competencies. It also reveals didactic conditions, interactive methods and the guiding role of the teacher that encourage students to participate freely and actively.
Keywords: Improvisational environment, student activity, creative thinking, independent learning, interactive methods, pedagogical approach, communicative competence, motivation, educational effectiveness, active learning.